Analisis Dasar Pertimbangan Hakim Pelaku Perbuatan Berlanjut Tindak Pidana Penipuan Investasi dan Tindak Pidana Pencucian Uang (Studi Terhadap Putusan Nomor 336/Pid.B/2023/PN Jkt.Pst) (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This study analyzes the judicial considerations in sentencing a perpetrator of money laundering originating from investment fraud, using the case of Decision Number 336/Pid.B/2023/PN Jkt.Pst as a reference. The defendant, Iwan Sabar, was proven to have employed a sophisticated scheme involving multiple fictitious entities to deceive victims and conceal the proceeds of crime. The analysis reveals that the judge applied a systematic legal and factual approach, including the principles of continuous acts (voortgezette handeling) and concursus realis between fraud and money laundering. In terms of penal objectives, the ruling reflects retributive and deterrent goals through a 10-year prison sentence and a fine of IDR 4 billion. However, rehabilitative and restorative aspects remain underdeveloped due to the absence of specific rehabilitation programs and a lack of clear mechanisms for victim compensation. Therefore, it is recommended that penal policies for economic crimes emphasize not only punishment but also victim recovery and offender reform in alignment with modern criminal justice principles.